A multi-axial vibration fatigue evaluation procedure for welded structures in frequency domain. (15th March 2022) - Pei, Xianjun; Krishnan Ravi, Sandipp; Dong, Pingsha; Li, Xiangwei; Zhou, Xiaokun
Graphical abstract: Highlights: We present a frequency domain procedure to model multiaxial fatigue of welded structures. Mesh insensitive traction stress method is applied to address the stress singularity at the welds. Traction stress mode shape and modal decomposition is used to compute the weld line dynamic stress. A correlation coefficient function can address non-proportional multiaxial stress effects. The method can identify the most detrimental mode in terms of fatigue for optimizing fatigue design. Abstract: Modeling of vibration fatigue of welded structures in the frequency domain can be particularly challenging. For instance, the stress singularity at weld locations causes finite element size sensitivity in stress determination. Furthermore, the interactions of multiple vibration modes at a weld location can generate non-proportional multiaxial stresses. Here we present a comprehensive procedure for modeling multiaxial fatigue behaviors of welded structures in the frequency domain to address some of these issues. The procedure utilizes a robust mesh-insensitive method and modal decomposition approach to determine the normal and shear traction stress responses. We proposed a non-proportionality correlation function to interrelate the resulting power spectrum density (PSD) of normal and shear traction stresses and their cross-PSD (CPSD) for establishing an effective stress parameter. The correlation function is determined and validated based on the well-established time-domain path-dependent maximum range (PDMR) method through a small-scale data-driven approach.